Characterization of PVA Fiber-Reinforced Pervious Concrete with Blended Recycled Ceramic Aggregates and Natural Aggregate - Qidan Xiao; Liuyang Feng; Yapei Xia; Fandong Xu (Advances in Materials Science and Engineering)
Effective industrial waste management is one of the important challenges facing modern society. Ceramic wastes occupy an important proportion of industrial waste. The utilization of waste of ceramics is becoming more and more attractive for many researchers to alleviate the environmental impact of industrial waste. As a low-impact development method, pervious concrete (PC) received more and more attention from researchers in recent years. However, the relatively low strength compared with ordinary concrete restricts the application of pervious concrete. This research used recycled ceramic coarse aggregates (RCCA) to partially replace natural coarse aggregates (NCA) to prepare recycled ceramic coarse aggregate pervious concrete (RCCAPC) and fiber-reinforced RCCAPC incorporating polyvinyl alcohol (PVA) fibers, and the effect of the replacement rate of RCCA and the amount of PVA fiber on the mechanical properties and permeability was investigated. The results show that RCCA can improve the mechanical properties of PC at a low substitution rate, as well as PVA fiber, and when the PVA content is about 0.3%, the enhancement effect is the best. Both RCCA replacement rate and PVA fiber content have little effect on the permeability coefficient of PC. Based on described studies, using RCCA to partially replace NCA at a low substitution rate is suitable for the preparation of PC, and PVA fibers can enhance the strength of PC, which may help to broaden the application scenarios of PC.